Changes in Body Composition Among Young Adults from Bydgoszcz (Poland) in 2021–2025: A Report on Secular Trends - Lewandowski, Andrzej; Siedlaczek, Marcin; Siedlaczek, Aleksandra; Piekorz, Zuzanna (Journal of Education, Health and Sport, 2026)
Objective: The aim of the study was to assess changes in somatic types according to the Wanke–Kolasa classification among physiotherapy students between 2021 and 2025 and to analyze the influence of selected socio-urbanization factors on the somatic structure of the studied population. Materials and Methods: The study included 574 first-year physiotherapy students from Bydgoszcz, including 207 men and 367 women. Based on anthropometric measurements, five typological indices constituting the basis of the Wanke–Kolasa somatic classification were calculated. Selected socio-urbanization factors were also analyzed. Descriptive statistics, the Mann–Whitney U test with Bonferroni correction, and the Jonckheere–Terpstra test were applied. Results: The studied population was dominated by components corresponding to a slender and relatively athletic body build. Both women and men demonstrated slight fluctuations in individual somatic components; however, no significant monotonic trends over time were observed. Mixed somatic types occurred more frequently than homogeneous profiles. Socio-urbanization factors showed no significant influence on somatic structure, except for a local association between maternal education level and the “H” component among women. Conclusions: The somatic structure of physiotherapy students during the analyzed period demonstrated high stability. The obtained results indicate limited variability of morphological traits in young adults after the completion of biological maturation and suggest a greater role of biological factors and lifestyle than classical socioeconomic determinants in shaping somatotype.